PENGARUH UPAH MINIMUM DAN DISITRIBUSI PENDAPATAN TERHADAP JUMLAH PENDUDUK MISKIN JAWA TIMUR - Satria Yuda Anggriawan; Aris Soelistyo; Dwi Susilowati (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2016)
This study aims to determine the relationship between the minimum wage and the income distribution of the poor. This research is a quantitative research using panel data, data used in the form of time series (2010-2014) and cross-section (29 districts and 9 cities in East Java). The data used in this study are secondary data obtained from the Central Statistical Agency (BPS) and the journal as a supporter. The analytical method used is the linear regression analysis of data using the software toolbox used common effect EViews 6. The results showed that the number of poor people in the neighborhood / city in the East Java period 2010-2014 decreased in An average of 5,088,144, minimum wage positive and significant variable impact on poverty and income distribution and a significant positive effect on the number of poor people in the neighborhood / city in East Java province